ECONOMY OF UZBEKISTAN: IS DEDOLLARIZATION REAL?. - Numanov K.K (Journal of Artificial Intelligence and Digital Economy, 2024)
The use of foreign currency (mainly the US dollar) preferentially over the national currency in Uzbekistan, in addition to international payments within the republic, creates serious problems for the national economy. It leads to an outflow of investment, reduces the level of economic development, minimizes budget profitability, which reduces the size of allocations to important sectors of the economy and social sphere.